The Assyrian Dictionary of the Oriental Institute of the University of Chicago. Vol. 20: U and W. (2010)
Edited by Martha T. Roth, with the assistance of Timothy J. Collins, Hermann Hunger, Remigius Jas, Jennie Myers, Erica Reiner†, and Joan Goodnick Westenholz. Manuscript Editor Linda McLarnan.